Teachers’ perspectives on grouping poorly performing learners in the same classroom - Lebohang Victoria Mulaudzi (Interdisciplinary Journal of Education Research, 2025)
Grouping poorly performing learners together in classrooms is a widespread yet contentious practice, often adopted to address diverse academic needs but criticised for perpetuating inequities. Limited studies focus on teachers’ perspectives, particularly in South Africa, where resource constraints and systemic pressures complicate classroom management. Thus, this study examines teachers’ perspectives on grouping poorly performing learners in the same classroom. Grounded in Vygotsky’s Theory of Social Development, the study applies the concepts of the Zone of Proximal Development and scaffolding to evaluate how grouping aligns with or contradicts social constructivist principles of peer-assisted learning. Adopting a transformative paradigm, the study employs a qualitative exploratory design to analyse teachers’ views shared on TikTok. The population comprised 346 publicly available comments on a video discussing classroom grouping; through purposive sampling, 32 comments were selected for relevance and diversity. Thematic analysis was used to code and interpret data, ensuring rigour via an audit trail and iterative theme refinement. Findings revealed, among others, the following key themes: simplifying instruction and classroom management; targeted teaching and curriculum pacing; influence of school policies and systemic pressures; challenges and drawbacks of grouping poor performers; and alternative strategies and perspectives. While teachers perceived short-term benefits, the practice often undermined peer learning and inclusivity. The study recommends professional development for differentiated instruction, mixed-ability grouping to leverage peer scaffolding, and policy reforms to address systemic barriers. By bridging theory and practice, the findings advocate for strategies that balance managerial needs with equitable, constructivist pedagogy.